Hubungan Tingkat Pengetahuan Dengan Sikap Seksual Pranikah Pada Remaja Kelas XI SMK N 1 Dlingo - Yuliasri, Tita Restu; Alfi Fadila , Septaria; Tri Susilani , Amalina; Ratnaningsih , Dwi (Agribiohealth (Journal of Agriculture, Biology & Health Sciences), 2025)
Indonesian adolescents face growing risks of engaging in premarital sexual behaviors, including kissing, touching, and sexual intercourse, which may result in unwanted pregnancy, unsafe abortion, and sexually transmitted infections. Limited knowledge about premarital sex increases adolescents’ vulnerability to peer pressure and social media influence. Adequate knowledge is therefore essential for forming responsible sexual attitudes. This study aimed to analyze the relationship between knowledge levels regarding premarital sexual activity and premarital sexual attitudes among eleventh-grade students at SMK N 1 Dlingo. This observational analytical study used a cross-sectional design. Total sampling was applied, involving all 199 eleventh-grade students as respondents. Data were collected using a validated and reliable questionnaire. Statistical analysis was performed using the Chi-Square test with SPSS software. Results showed that 168 students had good knowledge, 15 had sufficient knowledge, and 16 had insufficient knowledge. Regarding attitudes, 134 students demonstrated positive attitudes toward premarital sex, while 65 demonstrated negative attitudes. Bivariate analysis produced a p-value of 0.000, indicating a significant relationship between knowledge level and premarital sexual attitudes among adolescents. These findings emphasize the importance of school-based sexual education to promote informed attitudes and prevent risky behaviors among Indonesian adolescents today.